EAPH-05. MOLECULAR PROFILING AND IDENTIFICATION OF TARGETED THERAPIES FOR CHILDREN AND YOUNG ADULTS WITH PRIMARY CENTRAL NERVOUS SYSTEM TUMOURS IN THE UNITED KINGDOM. Issue 2 (22nd June 2018) - Wasti, Ajla; Carceller, Fernando; George, Sally; Koutroumanidou, Eleni; Izquierdo, Elisa; Guerra, Pilar; Zarowiecki, Magdalena; Campbell, James; Al-Lazikani, Bissan; Marshall, Lynley; Jones, Chris; Clarke, Matthew; et al.
Abstract: BACKGROUND. Molecular alterations: point mutations, amplifications and deletions give cells the ability to bypass therapeutic approaches. Molecular profiling facilitates access to personalised strategies to treat patients harbouring such alterations. METHODS. A Next Generation Sequencing (NGS) panel comprising 78 genes (version1) or 92 genes (version2) has been piloted in the UK since March 2016, using formalin-fixed paraffin embedded tissue of children and young adults with solid tumours, including central nervous system (CNS) tumours. RESULTS. Of 156 cases profiled, patients with primary CNS tumours constituted the largest subset (59 patients; 38%). Main diagnoses included high grade astrocytoma (22 patients; 37%), ependymoma (8 patients; 14%) and medulloblastoma (8 patients 14%). In 66% of sequenced samples the panel detected at least one genetic alteration and a total of 54 distinct genetic alterations were uncovered; most frequently in TP53 (16; 14%), H3F3A (8; 7%) and ATRX (7; 6%). In 2 cases (3%), identification of therapeutic targets (BRAF mutations) led to treatment with a combination of BRAF and MEK inhibitors via compassionate access programmes in young adults who had exhausted standard treatment options and were beyond the age eligibility cut-off for enrolment in the ongoing paediatric BRAF/MEK inhibitor studies. CONCLUSIONS. Molecular profiling is increasingly being integrated into standard of care for patients with CNS tumours. However, the finding of truly actionable mutations with available targeted therapies remains limited in clinical practice. More efficient approaches to implement personalised medicine strategies for CNS tumour patients are still needed as is currently illustrated by initiatives such as ESMART (NCT02813135).